Metaphysics in Nicolai Hartmann and Ludwig Wittgenstein - Adamek, Mateusz (Folia Philosophica, 2010)
The Paper deals with the relation between Hartmann’s and Wittgenstein’s understanding of the notion of „metaphysics”. The main thesis is as follows: despite Kantian sources of both points of view, Hartmann’s and Wittgenstein’s concepts should be conceived as independent.